Spatio-temporal variation of the ichthyofauna in Xel-Ha, Mexican Caribbean Marine Park and its relationship to physico-chemical parameters - Aldana Moreno, Alejandro (2016)
Xel-Ha is a private marine park where the extraction of flora and fauna is not allowed. Here, reef fish are one of the main touristic attractions, but there are no published surveys focused on fish community in this site. In this study we analyzed the spatio-temporal variation of the fish community in different areas of the marine park Xel-Há. Abundance and richness were estimated during one-year period (2012-2013); visual censuses using fixed transects of 100x5 m each distributed in 21 transects along five sites were established in different zones: “Bocana”, “Center”, “North branch”, “Cave” and “River”, including the inlet mouth to the sea, brackish mangrove channels and a zone with freshwater influence. To characterize the fish community, we used species richness, abundance, diversity, and density compared among zones and climatic seasons (rain, “norths” and dry). The similarity among zones and seasons was estimated using a multidimensional scaling analysis. The replacement on the species composition among seasons and sites was realized based on the presence-absence of fish. The influence of physicochemical variables such as temperature, salinity and dissolve oxygen concentration in the fish community was estimated by a principal component analysis. A total of 22 641 individuals were recorded corresponding to sixty-three species over the year. Abundance was higher during the windy season (locally named “norths”) with 7 991 organisms. The most representative species according with abundance and frequency of occurrence were: Haemulon sciurus, H. flavolineatum, Lutjanus griseus, Acanthurus coeruleus, Abudefduf saxatilis, and Gerres cinereus. Diversity increased from the rainy to the dry season; species richness and diversity was lower in “River” than other sites in Xel-Ha. Most species (54 %) species were residents through the year. Four non-shared species were observed during the rainy season and three in dry season. Dissolved oxygen was the most influential variable on the fish community composition among zones. Xel-Ha houses nearly 20 % of fish biodiversity reported for the mexican Caribbean, and the predominance of juveniles of several species confirms its role as a nursery area.